PODCAST, PARTICIPAÇÃO SOCIAL E DESENVOLVIMENTO - Lenharo, Rayane Isadora [UNESP]; Cristovão, Vera Lúcia Lopes (Faculdade de Educação da Universidade Federal de Minas Gerais, 2016)
This paper aimed to analyze the interaction between English teachers in continuing education and the media podcast as a tool in the process of teaching and learning English language. The data analyzed is derived from the transcription of a course focused on the use of technology applied to foreign languages' teaching. Our study is based on Bronckart's Social Discursive Interactionism and on the implications from the use of new technologies as tools that stimulate social participation. In a broader context, the interaction among the in-service teachers was based on Sinclair and Coulthard's IRA sequences. At the level of the context of production, the participants' acts were classified according to three categories. The results show that there is little engagement from the teachers, as they rarely initiate IRA sequences. In addition, the data reveal the existence of resistance in the teachers' learning concerning the new technologies issue.

Esta pesquisa objetivou analisar as interações de professores de inglês em formação continuada com a mídia podcast como um instrumento no processo de ensino-aprendizagem de língua inglesa. Os dados são provenientes da transcrição de um curso sobre novas tecnologias aplicadas ao ensino. Ancoramos a investigação no Interacionismo Sociodiscursivo de Bronckart e nas implicações do uso de novas tecnologias como ferramentas de participação social. No contexto amplo, a interação dos participantes foi investigada por meio das sequências IRA com base em Sinclair e Coulthard. Já no nível da situação de produção, o agir dos participantes foi categorizado por meio de três tipos de agir. Os resultados obtidos mostram que, de um modo geral, os participantes se colocam no papel de aprendizes e evitam se arriscar, já que raramente iniciam sequências IRA. Além disso, os dados revelam a existência de certa resistência no aprendizado dos professores com relação ao tema novas tecnologias.
PODCAST, SOCIAL PARTICIPATION AND DEVELOPMENT
Keywords: Text genres; Continuing education; Sociodiscursive Interactionism; Podcast; Gêneros textuais; Formação continuada; Interacionismo Sociodiscursivo; Podcast.